New Criminal Offences Protecting the Environment and Their Qualifying Circumstances (Articles 3, 8 and 9 of EU Directive 2024/1203) - Đokić, Ivan (Glasnik Advokatske komore Vojvodine, 2026)
The insufficiently precise normative framework established by the Environmental Crime Directive 2008/99/EC, as well as the unsatisfactory and modest effects of its implementation, prompted the proposal to improve the regulatory framework of the European Union in the field of environmental protection. This ultimately resulted in the adoption of the new Directive on the protection of the environment through criminal law 2024/1203, in mid-April 2024. In addition to significantly increasing the number of criminal offences, clarifying their qualified forms, providing detailed lists of aggravating and mitigating circumstances, and setting out more specific provisions on criminal sanctions, the Directive introduces a series of new solutions aimed at improving cross-border cooperation, as well as coordination and cooperation among competent authorities within each Member State. However, a revolutionary change lies in the way the Directive defines the relationship between criminal and administrative law. It is well known that criminal-law provisions in the domain of environmental protection are predominantly of a blanket nature, given that certain conduct becomes criminal only when it violates a relevant environmental protection rule. In this respect, criminal law has traditionally been linked to administrative law, which, through various acts, determines the threshold values of permissible environmental impact and, through numerous individual permits and authorisations, excludes the unlawfulness of specific actions affecting the environment. Similarly, for all criminal offences introduced by the new Directive, the requirement remains that the conduct in question must constitute an unlawful act. Yet, under the new definition, conduct is considered unlawful not only when it breaches EU law, but even when it is carried out on the basis of a decision by a competent authority of a Member State, if that authorisation was obtained through fraud, corruption, extortion, coercion, or if such authorisation manifestly violates relevant substantive legal requirements. Although this legal innovation is intended as a tool for achieving more effective criminal-law protection in the field of environmental protection, the question remains how Member States will incorporate this concept into their national legislation – a concept which, regardless of any criminal-policy justification, poses a serious risk to the principle of legality, which requires that the conditions for criminal liability be precisely and clearly defined. Moreover, the seemingly “iron rule” that criminal law must not sanction what another field of law explicitly permits appears to have lost its former value. It seems that the drafter of the Serbian Draft Law on Amendments to the Criminal Code of 2025 has shaped the new criminal offences concerning the protection of the environment in a highly satisfactory manner, avoiding some of the vague and contentious formulations contained in the aforementioned Directive.